Special education provision in China – Characteristics and challenges as perceived by stakeholders - Alduais, Ahmed; Deng, Meng (Specijalna edukacija i rehabilitacija, 2022)
Introduction. China provides special education students with the possibility of indirect enrolment in regular education (inclusion), attendance at special classes and regular education classes (mainstreaming), admission to special education schools (segregation), or admission to home education (exclusion). This promising large system of education has several shortfalls, such as the inadequacy of curriculum, the rivalry between segregation and inclusion trends, teacher preparation, and parents’ awareness of their children’s needs. Objectives. In-depth interviews were conducted to uncover these strengths and shortcomings from the perspective of Chinese stakeholders. Methods. Nine in-depth interviews were conducted with special education stakeholders in China. Results. Our findings present a detailed analysis that provides a visual summary of the main strengths, weaknesses, and suggestions for improvement, as well as specific features relevant to the Chinese context. Conclusion. The results of our study furthered this discussion by revealing our participants’ long experience in the field and highlighting some of the current gaps – curriculum, teacher training, the rivalry between special education and inclusive education, and the need to increase parents’ awareness of their children’s rights in advance of a more inclusive society.